PERBEDAAN MENGUNYAH BUAH APEL DAN PIR TERHADAP PENURUNAN PLAK SKOR - andriani, meili; danan, danan; ulfah, rasuna (JURNAL TERAPIS GIGI DAN MULUT, 2022)
Riskesdas (2013), recorded the percentage of Banjarbaru residents whohave dental and mouth problems of 25.2%. The prevalence of active caries is 53.8%.Caries is the result of interactions of bacteria on the surface of teeth, plaque or biofilmsand diets (especially carbohydrate components that can be fermented by plaquebacteria to become acidic, especially lactic and acetic acid) so that demineralization ofdental tissue occurs and requires sufficient time for its occurrenceThis study aims to determine the difference between chewing apples andpears on the decrease in plaque scores. This type of research is a library research(Library Researc). Data collection techniques in this study are documentation, which islooking for data about things or variables in the form of theses and journals related tochewing apples and pears against plaque score reduction.The results of this study were obtained based on several studies and journalsstating that there were differences in chewing apples and pears on the decrease inplaque scores.The conclusions of this study indicate that there are differences in chewingapples and pears on the decrease in plaque scores. It is recommended that healthworkers make preventive efforts to the public, the community is advised to consumefruits that are fibrous and watery one of which is apples and pears that are useful forcleaning the oral cavity and lowering plaque.